Exclusivity in online targeted promotions: cross-cultural preferences of consumers. (2018) - Broeder, Peter; Derksen, Rendal
The ease of adapting and customising content leads targeted promotions to be one of the most important strategies in online marketing. Online marketers use different strategies to attract consumers to their webshop, such as scarcity effects. A specific type of scarcity is exclusivity, in which only a selected group of people receives a promotion. This study examines the effectiveness of the use of online targeted promotions across cultures. 140 Dutch and 123 Mexicans between 18 and 35 years old filled out an online questionnaire. Participants were randomly assigned to one of the four conditions in which they received either an exclusive or a non-exclusive offer on either Facebook or Gmail. The results indicated that Mexicans are more prone to exclusive offers than non-exclusive offers, while for Dutch consumers an opposite trend was found. Mexicans report a more favourable attitude and higher visiting intention for online advertisements in general, although the found effect was especially strong for exclusive offers. This study shows that the use of exclusivity can be effective in emerging online markets such as Mexico. However, new ways of online advertising are needed to persuade the experienced online consumer.